Microplastic Shape, Polymer Type, and Concentration Affect Soil Properties and Plant Biomass - Lozano, Yudi M.; Lehnert, Timon; Linck, Lydia T.; Lehmann, Anika; Rillig, Matthias C. (Frontiers in Plant Science, 2021)
Microplastics may enter the soil in a wide range of shapes and polymers. However, little is known about the effects that microplastics of different shapes, polymers and concentration may have on soil properties and plant performance. To address this, we selected twelve microplastics representing different shapes (fibers, films, foams, fragments) and polymers, and mixed them each with soil at a concentration of 0.1%, 0.2%, 0.3%, 0,4%. A phytometer (Daucus carota) grew in each pot during four weeks. Shoot, root mass, soil aggregation and microbial activity were measured. All shapes increased plant biomass. Shoot mass increased by ~ 27% with fibers, ~ 60% with films, ~ 45% with foams and by ~54% with fragments, as fibers hold water in the soil for longer, films decrease soil bulk density, foams and fragments can increase soil aeration and macroporosity, which overall promote plant performance. By contrast, all shapes decreased soil aggregation by ~25% as microplastics may introduce fracture points into aggregates and due to potential negative effects on soil biota. The latter may also explain the decrease in microbial activity with, for example, polyethylene films. Our findings show that shape, polymer type and concentration are key properties when studying microplastic effects on terrestrial systems.